Assessing Sentiment in YouTube Video Content: A Title and Description Analysis Approach to Analyze User Reactions - Sanyour, Rawan; Abdullah, Manal; El Emary, Ibrahiem M. M. (International Journal for Applied Information Management, 2024)
This study investigates the relationship between sentiment in YouTube video titles and descriptions and user engagement metrics, such as view count, like count, and comment count. The findings reveal that videos with positive sentiment generally attract higher levels of engagement, including more views, likes, and comments, while videos with negative sentiment typically receive lower interaction levels. The research emphasizes the importance of emotionally resonant content, suggesting that content creators should focus on producing videos with positive emotional tones to maximize audience interaction. Additionally, the study highlights the significance of well-crafted titles and descriptions as key drivers of engagement, as these textual elements influence viewers' initial expectations and emotional reactions. However, the study is limited to analyzing titles and descriptions, which may not fully capture the emotional tone of the video itself. Future research should incorporate the actual video content and explore additional engagement metrics, such as shares and watch time, for a more comprehensive understanding of viewer behavior. Despite these limitations, the study provides valuable insights that can guide content creators in tailoring their video content and metadata to foster greater viewer engagement and content success.